The empirical investigation on factor that affect the housing price in Malaysia / Nur Amirah Othman - Othman, Nur Amirah (Faculty of Business and Management, 2016)
The aim of this study is to investigate the relationship between Consumer Price Index, Base Lending Rate and Population to the Malaysia housing price. The study used Single Linear Regression and Multiple Linear Regression in order to find the relationship among those variables. The quarterly data of all variable is collected from 1st Quarter 2000 until 4th Quarter 2014. From the result, it reveals that not all these variables have a significant positive relationship towards Malaysia House Price Index. The result indicates that only the base lending rate are not significantly with Malaysia House Price Index. These results further our understanding of the relationship between the Malaysia House Price Index and should be useful for regulator, investor and speculator.